The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1101/2021.03.30.21254587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing the countrywide epidemic spread of influenza A(H1N1)pdm09 virus in Kenya between 2009 and 2018

Abstract: Background: The spatiotemporal patterns of spread of influenza A(H1N1)pdm09 viruses on a countrywide scale are unclear in many tropical/subtropical regions mainly because spatiotemporally representative sequence data is lacking. Methods: We isolated, sequenced, and analyzed 383 influenza A(H1N1)pdm09 viral genomes isolated from hospitalized patients between 2009 and 2018 from seven locations across Kenya. Using these genomes and contemporaneously sampled global sequences, we characterized the spread of the v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Studies of college campuses using phylogenetic methods have revealed extensive mixing of influenza virus strains among college students [23]. City-wide and countrywide, transmission of influenza in a season is characterized by majorly multiple virus introductions into cities [21] and countries [24][25][26]; viruses then spread from multiple geographical locations to multiple geographical destinations following introduction [24][25][26]. However, there is a paucity of studies that describe the patterns of spread of influenza on a local scale (city or town) due to sparsity of representative spatiotemporal sequence data from defined sub-populations residing in the same geography within a country [21,27].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of college campuses using phylogenetic methods have revealed extensive mixing of influenza virus strains among college students [23]. City-wide and countrywide, transmission of influenza in a season is characterized by majorly multiple virus introductions into cities [21] and countries [24][25][26]; viruses then spread from multiple geographical locations to multiple geographical destinations following introduction [24][25][26]. However, there is a paucity of studies that describe the patterns of spread of influenza on a local scale (city or town) due to sparsity of representative spatiotemporal sequence data from defined sub-populations residing in the same geography within a country [21,27].…”
Section: Introductionmentioning
confidence: 99%